2008
DOI: 10.1111/j.1743-6109.2008.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Phosphodiesterase Type 5 Inhibitors: Nonerectogenic Beneficial Uses

Abstract: Introduction Phosphodiesterase type 5 (PDE5) hydrolyses cyclic guanylate monophosphate (cGMP) specifically to 5′ GMP. PDE5 inhibitors were a breakthrough medication that addressed a previously unfulfilled medical need. They promoted vascular relaxation in the corpora cavernosa and penile erection during sexual stimulation. Sildenafil, vardenafil, and tadalafil were approved then introduced as effective treatments for male erectile dysfunction. This impact has stimulated academic, clinical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 141 publications
(210 reference statements)
2
26
0
1
Order By: Relevance
“…(109)) are cGMP-specific PDE5 (EC3.1.4.17) inhibitors currently used for the treatment of male erectile dysfunction [900][901][902][903][904]. PDE5 is responsible for degradation of cGMP in the corpus cavernosum in the penis.…”
Section: Phosphodiesterase Type 5 (Pde5) Inhibitorsmentioning
confidence: 99%
“…(109)) are cGMP-specific PDE5 (EC3.1.4.17) inhibitors currently used for the treatment of male erectile dysfunction [900][901][902][903][904]. PDE5 is responsible for degradation of cGMP in the corpus cavernosum in the penis.…”
Section: Phosphodiesterase Type 5 (Pde5) Inhibitorsmentioning
confidence: 99%
“…Apart from the efficacy of PDE5 inhibitors in the treatment of erectile dysfunction or pulmonary arterial hypertension (Mostafa, 2008), experimental data show that sildenafil enhances angiogenesis and neurogenesis and improves functional outcome during stroke recovery (Ding et al, 2008), improves learning and memory in the Tg2576 model of Alzheimer's disease and in a senescence accelerated mouse model (Cuadrado-Tejedor et al, 2011;Orejana et al, 2011), and prevents the neurotoxic effects of 3-nitropropionic acid (Puerta et al, 2010a). Moreover, we have recently shown that sildenafil given shortly before MDMA affords complete protection against MDMA-induced 5-HT depletions by opening mitochondrial ATP-sensitive K 1 channels, a key mechanism involved acute preconditioning paradigms (Puerta et al, 2009b).…”
mentioning
confidence: 99%
“…(2) Psychological counseling, education, and lending a patient ear are the cornerstones of FSD evaluation [52]. (3) Counseling the male partner and treating him if there are any complain of erectile dysfunction [53,54].…”
Section: Recommended Treatment Optionsmentioning
confidence: 99%